Process-induced formation of imidazoles in selected foods. (1st August 2017) - Mottier, Pascal; Mujahid, Claudia; Tarres, Adrienne; Bessaire, Thomas; Stadler, Richard H.
Highlights: Three imidazoles were quantified by isotope dilution LC-MS/MS in heated foods. Highest 4-methylimidazole levels were present in roasted cereals and cocoa powders. Medium and dark toasted bread revealed quantifiable amounts of 4-methylimidazole. Alkylimidazoles are not reliable markers of caramel colorings addition to foods. Abstract: The presence of 4-methylimidazole (4-MEI), 2-methylimidazole (2-MEI) and 2-acetyl-4-tetrahydroxybutylimidazole (THI) in some foods may result from the usage of caramel colorants E150c and E150d as food additives. This study demonstrates that alkylimidazoles are also byproducts formed from natural constituents in foods during thermal processes. A range of heat-processed foods that are known not to contain caramel colorants were analyzed by isotope dilution LC-MS/MS to determine the contamination levels. Highest 4-MEI concentrations (up to 466 µg/kg) were observed in roasted barley, roasted malt and cocoa powders, with the concomitant presence of 2-MEI and/or THI in some cases, albeit at significantly lower levels. Low amounts of 4-MEI (<20 µg/kg) were also detected in cereal-based foods such as breakfast cereals and bread toasted to a brown color (medium toasted). The occurrence of 4-MEI in certain processed foods is therefore not a reliable indicator of the presence of the additives E150c or E150d.